Inclusive Strategy for Small and Marginal Farmers in Tapioca Production, Processing and Marketing - Sendilkumar, R; Arya, S (Journal of Agricultural Extension Management, 2018)
This study was conducted to explore the post-harvest value addition opportunities tapioca, identify the constraints faced by small and marginal farmers in processing and to suggest a strategy. Primary data from 60 tapioca farmers of Elamadu Grama Panchayath of Kollam district, Kerala were collected through interview schedule. Expert opinion was collected from the Scientists of Kerala Agricultural University (KAU), KVK, and CTCRI etc. to screen the appropriate technology for tapioca value addition. The data obtained were analysed using percentage analysis, SWOC and COWS analysis. It was found that a number of farmers were involved in tapioca cultivation and could produce marketable surplus, but were not engaged in any post-harvest value addition activities. Indeed, farmers have expressed their willingness to start value addition jointly as a group. The technocrats opined that tapioca snacks and chips are better options for value addition at farm level. The study highlighted the need for an exclusive organisation for tapioca cultivation, marketing and processing. Initiating farmer driven producer organisations and consumer linked value chain would be a promising strategy for livelihood of small and marginal farmers of tapioca.